2014
DOI: 10.1186/1472-6920-14-208
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological beliefs and therapeutic health concepts of physiotherapy students and professionals

Abstract: BackgroundHealth knowledge develops fast and includes a lot of ambiguous or tentative information. In their daily routine, both health care students and professionals continuously have to make judgments about the viability of health knowledge. People’s epistemological beliefs (EBs) and their therapeutic health concepts are factors that influence how they deal with health knowledge. However, very little is known about the occurrence of these factors at different stages of people’s career. The present study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 41 publications
(48 reference statements)
10
30
0
Order By: Relevance
“…In accordance with the cross-sectional study [29] an additional explorative analysis disclosed that first-year students showed greater development (M Diff =0.82± 0.56) than the advanced students (M Diff =0.39± 0.66) regarding medicine-related EBs, t(40)=1.97, P = 0.028, d=0.70 (Mann-Whitney-Utest: U=105.00, P = 0.024).…”
Section: Health-related Ebssupporting
confidence: 76%
See 3 more Smart Citations
“…In accordance with the cross-sectional study [29] an additional explorative analysis disclosed that first-year students showed greater development (M Diff =0.82± 0.56) than the advanced students (M Diff =0.39± 0.66) regarding medicine-related EBs, t(40)=1.97, P = 0.028, d=0.70 (Mann-Whitney-Utest: U=105.00, P = 0.024).…”
Section: Health-related Ebssupporting
confidence: 76%
“…Sample items of this scale are "sorted -unsorted" or "absolute -relative", whereby "unsorted" and "relative" represented sophisticated EBs (see Table 1). The bm and bps health concepts were measured following the procedure presented previously [17,29]. Participants rated the importance of five representative bm terms, such as "diagnosis", and five characteristic bps concepts, such as "functionality", on six-point Likert scales ranging from 1 (not important) to 6 (very important) (see Table 2).…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers should take into consideration epistemic aims and epistemic values that contribute to nuances in individuals’ conceptions and behavior 5 . Also, while few studies examine epistemic cognition in other health fields, there is evidence that sophistication of epistemic beliefs with experience occurs across professions 67 , 68 . Studies comparing epistemic orientations including biomedical or biopsychosocial orientations 68 or patterns of knowing for practice among medical, nursing and allied health fields 69 , 70 , 71   could provide further insights for both medical and inter-professional education.…”
Section: Discussionmentioning
confidence: 99%